Dimensionamento de estrutura composta por perfis e chapas de madeira (wood frame) - Freitas, Fernando Gabriel Campos (Universidade Federal Rural do Semi-Árido, 2018)
Wood Frame is a constructive system that consists of the use of wood as a structural element of a building, replacing the more conventional ones that are the reinforced concrete and the steel. In Brazil this system is still little used, but over the years it has been gaining more and more space in the civil engineering market. One of the difficulties in carrying out projects in Wood Frame is the lack of a national standard to be followed that explains in detail how to execute such a project, as it exists for steel structures or reinforced concrete, and it is necessary to use foreign standards such as the US NDS standards, therefore notes a shortage of qualified professional to perform the design of wooden structures. The present work has the objective to dimension in detail a residential building of 2 floors in Wood Frame based on the American norms of NDS compatible with the Brazilian standard of wood structures. For the calculations the requesting efforts were obtained from the modeling in SAP2000 computational software that works with finite elements and allows the user to obtain the requesting efforts in each piece of the structure which made it possible to locate the most requested building elements for the calculation of the resistances. Checking if the structure resists safely all the applicant efforts, besides helping professionals who wish to carry out this type of dimensioning, considering that in brazil there is little content on the subject.
Monografia
Keywords: Projeto estrutural; Wood Frame; SAP2000; ENGENHARIAS::ENGENHARIA CIVIL